2017
DOI: 10.1038/s41598-017-03981-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Angiopoietin Signalling by Soluble Tie2 Ectodomain and Engineered Ligand Trap

Abstract: Angiopoietin-1 (Angpt1) is a glycoprotein ligand important for maintaining the vascular system. It signals via a receptor tyrosine kinase expressed on the surface on endothelial cells, Tie2. This receptor can undergo regulated ectodomain cleavage that releases the ligand-binding domain (sTie2) into the circulation. The concentration of sTie2 is increased in a range of conditions, including peripheral arterial disease and myocardial infarction, where it has been suggested to bind and block Angpt1 resulting in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…In pathological angiogenesis, Tie2 signaling is not only attenuated by the antagonistic activity of Ang2, but VEGF also induces extracellular domain cleavage of Tie2 in a phosphoinositide-3 kinase/Akt-dependent manner, further diminishing the activity of Tie2 (Findley et al., 2007). In vitro , soluble Tie2 represses Tie2 signaling in a concentration-dependent manner (Alawo et al., 2017), consistent with the clinical observation that, among patients with peripheral arterial disease, the plasma level of soluble Tie2 distinguishes patients with intermittent claudication and those with critical limb ischemia, the more severe manifestation (Findley et al., 2008). In accordance with experimental findings, the model predicts the concentration-dependent inhibition of Tie2 activation by soluble Tie2 (Figure 2K) and the inhibitory effect of increasing the extracellular domain shedding rate of Tie2 (Figure S3A).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In pathological angiogenesis, Tie2 signaling is not only attenuated by the antagonistic activity of Ang2, but VEGF also induces extracellular domain cleavage of Tie2 in a phosphoinositide-3 kinase/Akt-dependent manner, further diminishing the activity of Tie2 (Findley et al., 2007). In vitro , soluble Tie2 represses Tie2 signaling in a concentration-dependent manner (Alawo et al., 2017), consistent with the clinical observation that, among patients with peripheral arterial disease, the plasma level of soluble Tie2 distinguishes patients with intermittent claudication and those with critical limb ischemia, the more severe manifestation (Findley et al., 2008). In accordance with experimental findings, the model predicts the concentration-dependent inhibition of Tie2 activation by soluble Tie2 (Figure 2K) and the inhibitory effect of increasing the extracellular domain shedding rate of Tie2 (Figure S3A).…”
Section: Discussionsupporting
confidence: 80%
“…Finally, the calibrated model reproduces the concentration-dependent inhibition effect of soluble Tie2 treatment on Tie2 activation by acting as a ligand trap as reported in Alawo et al. (Figure 2K) (Alawo et al., 2017). The parameters, observables, reactions, and the data used in the calibration are tabulated in Tables S1, S2, S3, and S4.
Figure 2Model Calibration Using Global Optimization(A and B) The concentration-dependent agonistic activity of (A) Ang1 and (B) Ang2.(C and D) Ang2 functions as partial agonist compared to Ang1.(E and F) Ang1 and Ang2 induce different receptor trafficking and turnover of Tie2.(G and H) Silencing orphan receptor Tie1 enhances Ang1- and Ang2-induced Tie2 activation.(I and J) Receptors Tie2 and Tie1 are constitutively shed from the cell surface and produce soluble receptors.(K) Soluble Tie2 induces concentration-dependent inhibition of Tie2 activation.
…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Notably, the presence of sTie2 has been documented in vivo ( 93 , 98 , 99 ) and its levels are significantly increased in septic versus non-septic Intensive Care Units (ICU) patients ( 100 ). However, recent evidence incorporating mathematical and in vitro experimental modeling suggests that the molar ratio of sTie2:Ang1 levels found in patients with severe sepsis would have little influence on Ang/Tie2 activation in vivo ( 101 ).…”
Section: The Ang/tie Pathway In Severe Bacterial Infectionsmentioning
confidence: 99%
“…Further in this regard, a recent study by Braun et al, 2020 reported that endothelial Tie2 activation limits diapedeses induced leakage. The cleavage of the Tie2 ectodomain prevents protective Angiopoietin-1-Tie2 ligation and the cleaved Tie2 receptor can even function as a ligand trap in the circulation further inhibiting protective Angpt-1 activity ( Alawo et al, 2017 ; Zhang et al, 2019 ). Besides these effects on Tie2 activation by ligands, we found that the inhibition of shedding to protect Tie2 surface expression is sufficient to ameliorate sepsis-induced vascular barrier breakdown.…”
Section: Discussionmentioning
confidence: 99%